Analisis Pengaruh Kinerja Keuangan, Leverage, Ukuran Perusahaan dan Sertifikasi Lingkungan Terhadap Kualitas Pengungkapan Lingkungan (Studi Empiris Pada Industri Pertambangan yang Terdaftar di BEI) - Amanda Oktariyani; Inten Meutia (AKUNTABILITAS, 2016)
This study aims to look at the effect of financial performance, leverage, company size and environmental certification on the quality of environmental disclosures. The population in this study was the mining industry that was listed on the Stock Exchange in the period 2011-2014. Based on the purposive sampling technique, there were 17 companies selected. The research data used is obtained from the company's annual report. The data analysis method used is panel data regression. The results showed that financial performance has a negative and significant influence on the quality of environmental disclosures, while leverage has a positive and significant effect. However, company size and environmental certification do not show a significant effect on the quality of environmental disclosures.